Analysis on land alienation status at Lembaga Kemajuaan Pertanian Muda [MADA] authority / Muhammad Adzim Marwan Abdul Aziz - Abdul Aziz, Muhammad Adzim Marwan (2018)
Land alienation status is very important to all people. People does not to know what will happen to the land alienation. This paper is about the research of analysis on the land alienation status at Lembaga Kemajuan Pertanian Muda (MADA) Authority. The area for the research are at region 1, PPK 1 on the MADA Authority which this area under the Lembaga Kemajuan Pertanian Muda (MADA). The data collected from the MADA organization and study area to complete the research. The aim for this research is to produce and analysis of land alienation status at MADA area by using software survey application. The objective for this research is to investigate the land alienation status regarding to Bumiputera and Non-Bumiputera, to analyses several factor and data related about ownership princple in MADA area and to represent the mapping land alienation status. The methodology and produce involve during this research was using ArcGIS software to analyses the factor to Bumiputera and Non-Bumiputera. The expected outcome will be produced and comparison of the Bumiputera and Non-Bumiputera. And from the result that will come out the analysis of the land alienatioan.